Facilitating engagement through strong relationships between primary healthcare and Aboriginal and Torres Strait Islander peoples. (14th August 2016) - Davy, Carol; Cass, Alan; Brady, John; DeVries, Joanne; Fewquandie, Barry; Ingram, Suzzane; Mentha, Ricky; Simon, Pamela; Rickards, Bernadette; Togni, Samantha; Liu, Hueming; Peiris, David; et al.
Abstract: Objective : Given the high prevalence of chronic disease, it is of concern that access to and sustained engagement with primary healthcare services by Aboriginal and Torres Strait Islander Australians is often far lower than would be expected. This study sought to explore ways in which relationships can support sustained engagement with healthcare services. Methods: Semi‐structured interviews were conducted with 126 Aboriginal and Torres Strait Islander participants with and without chronic disease and 97 Aboriginal and Torres Strait Islander and non‐Indigenous healthcare providers, healthcare service managers or administrative staff. Results : Our findings indicate that when faced with acute health issues, Aboriginal and Torres Strait Islander participants did prioritise care, provided that the service was both physically and emotionally welcoming. Trustworthiness of healthcare providers and strong relationships with patients were the most important factors for encouraging sustained engagement overtime. Conclusions : Responsibility for sustaining relationships does not rest solely with Aboriginal and Torres Strait Islander patients. Rather, healthcare providers need to commit to the process of building and maintaining relationships. Implications : First and foremost healthcare providers should take time to establish and then maintain relationships. Healthcare services can also contribute by ensuring facilities are welcoming for Aboriginal and Torres Strait Islander peoples.